The Complete Plastid Genomes of Seven Sargassaceae Species and Their Phylogenetic Analysis - Li, Ruoran; Jia, Xuli; Zhang, Jing; Jia, Shangang; Liu, Tao; Qu, Jiangyong; Wang, Xumin (Frontiers in Plant Science, 2021)
Sargassum is one of the most important genera of the family Sargassaceae in brown algae and is used to produce carrageenan, mannitol, iodine, and other economic substances. Here, seven complete plastid genomes of Sargassum ilicifolium var. conduplicatum, Sargassum graminifolium, Sargassum phyllocystum, Sargassum muticum, Sargassum feldmannii, Sargassum mcclurei, and Sargassum henslowianum were assembled using next-generation sequencing. The sizes of the seven circular genomes ranged from 124,258 bp to 124,563 bp, with two inverted regions and the same set of plastid genes, including 139 protein-coding genes (PCGs), 28 tRNAs, and 6 rRNAs. Compared to the other five available plastid genomes of Fucales, 136 PCGs were conserved, with two common ones shared with Coccophora langsdorfii, and one with Sargassum fusiforme and Sargassum horneri. Co-linear analysis identified two inversions of trnC(gca) and trnN(gtt) in ten Sargassum species, against S. horneri and C. langsdorfii. Phylogenetic analysis based on plastid genomes of 43 brown algae (Phaeophyceae) showed four clades, whose ancient ancestor lived around 41.8 million years ago (Mya), and the internal evolutionary branches in Fucales started to be formed 19.89 Mya, while Sargassum species were divided into two subclades 8.55 Mya. Our novel plastid genomes provided evidence for the speciation of brown algae and plastid genomic evolution events.